Transformers : meet the autobots - Frantz, Jennifer (New York : HarperCollins, 2007)
Introduces the Autobots, describing their abilities and providing details about their fight for the Allspark.
"2, reading with help."
"Based on the new movie!"--Cover.
1.9
K-3
K-3
Keywords: Transformers (Fictitious characters) -- Fiction; Science fiction; Robots -- Fiction; Good and evil -- Fiction; Transformers (Fictional characters) -- Fiction; Science fiction; Robots -- Fiction; Good and evil -- Fiction; Readers (Elementary)